The optical stretcher as a tool for single‐particle X‐ray imaging and diffraction. (15th June 2018) - Nicolas, Jan-David; Hagemann, Johannes; Sprung, Michael; Salditt, Tim
Abstract : An optical stretcher was used to trap and manipulate biological cells and latex beads in a microfluidic channel. The trapping capability was used to image isolated suspended cells using X‐ray phase‐contrast imaging. By rotation of the specimen, even the three‐dimensional phase shift of a cell could be recovered. Abstract : For almost half a century, optical tweezers have successfully been used to micromanipulate micrometre and sub‐micrometre‐sized particles. However, in recent years it has been shown experimentally that, compared with single‐beam traps, the use of two opposing and divergent laser beams can be more suitable in studying the elastic properties of biological cells and vesicles. Such a configuration is termed an optical stretcher due to its capability of applying high deforming forces on biological objects such as cells. In this article the experimental capabilities of an optical stretcher as a potential sample delivery system for X‐ray diffraction and imaging studies at synchrotrons and X‐ray free‐electron laser (FEL) facilites are demonstrated. To highlight the potential of the optical stretcher its micromanipulation capabilities have been used to image polymer beads and label biological cells. Even in a non‐optimized configuration based on a commercially available optical stretcher system, X‐ray holograms could be recorded from different views on a biological cell and the three‐dimensional phase of the cell could be reconstructed. The capability of the setup to deform cells at higher laser intensities in combination with, for example, X‐ray diffraction studies could furthermore lead to interesting studies that couple structural parameters to elastic properties. By means of high‐throughput screening, the optical stretcher could become a useful tool in X‐ray studies employing synchrotron radiation, and, at a later stage, femtosecond X‐ray pulses delivered by X‐ray free‐electron lasers.